2015
DOI: 10.1073/pnas.1401501112
|View full text |Cite
|
Sign up to set email alerts
|

Gustatory and metabolic perception of nutrient stress in Drosophila

Abstract: Sleep loss is an adaptive response to nutrient deprivation that alters behavior to maximize the chances of feeding before imminent death. Organisms must maintain systems for detecting the quality of the food source to resume healthy levels of sleep when the stress is alleviated. We determined that gustatory perception of sweetness is both necessary and sufficient to suppress starvation-induced sleep loss when animals encounter nutrient-poor food sources. We further find that blocking specific dopaminergic neur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
52
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(54 citation statements)
references
References 36 publications
2
52
0
Order By: Relevance
“…Indeed, we found that larval starvation impacted adult feeding behavior, measured as the gustatory perception of sugar. Gustatory perception is critical for animal survival, perhaps especially in a low-nutrient environment (Linford et al, 2015), as it helps an organism locate energy-rich food sources in order to maintain adequate nutrition (Drewnowski, 2000;Rohwedder et al, 2012). In our study, we observed reduced gustatory perception in the adult bees that experienced starvation as larvae.…”
Section: Discussion Adaptive Responses To An Anticipatory Starvationsupporting
confidence: 48%
“…Indeed, we found that larval starvation impacted adult feeding behavior, measured as the gustatory perception of sugar. Gustatory perception is critical for animal survival, perhaps especially in a low-nutrient environment (Linford et al, 2015), as it helps an organism locate energy-rich food sources in order to maintain adequate nutrition (Drewnowski, 2000;Rohwedder et al, 2012). In our study, we observed reduced gustatory perception in the adult bees that experienced starvation as larvae.…”
Section: Discussion Adaptive Responses To An Anticipatory Starvationsupporting
confidence: 48%
“…Hexanoic acid and sugars are detected by shared peripheral sensory neurons that are also known to regulate sleep . Therefore, it is possible that fatty acids promote sleep by providing nutrients, or through the activation of these sensory neurons.…”
Section: Resultsmentioning
confidence: 99%
“…Dietary nutrients can be perceived via peripheral processing by the taste system as well as by taste‐independent mechanisms . In the taste system, thermogenetically activating sweet sensing neurons labeled by the Gustatory receptor 64f is sufficient to restore normal sleep to starved flies . However, whether flies lacking sugar receptors suppress sleep on an all sugar diet have been conflicting .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Food is comprised of complex macronutrients including sugars, proteins, and fats. In flies, diet composition has been shown to impact sleep, but studies have primarily relied upon varying the concentrations of sugars and protein, or fully food-restricting animals (Catterson et al, 2010; Keene et al, 2010; Linford, Chan, & Pletcher, 2012; Linford, Ro, Chung, & Pletcher, 2015; Yamazaki et al, 2012). Flies have are capable of tasting a number of additional modalities including fatty acids, salt, amino acids, and carbonation (Fischler, Kong, Marella, & Scott, 2007; Masek & Keene, 2013; Toshima & Tanimura, 2012; Zhang, Ni, & Montell, 2013), but the effects of these factors on sleep regulation has not been explored.…”
Section: Introductionmentioning
confidence: 99%